2019
DOI: 10.1177/0363546519873856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fatty Acid–Binding Protein 4 Inhibition on Rotator Cuff Muscle Quality: Histological, Biomechanical, and Biomolecular Analysis

Abstract: Background: A rotator cuff tear (RCT) induces fatty acid–binding protein 4 (FABP4) expression, resulting in ectopic fat accumulation in the rotator cuff muscle. Purpose: To evaluate whether FABP4 inhibition reduces fatty infiltration and improves muscle physiology after RCT in a rat model. Study Design: Controlled laboratory study. Methods: Human supraspinatus muscle and deltoid muscle tissues were acquired from patients with RCTs during arthroscopic surgery, and FABP4 expression in the supraspinatus muscle wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
0
14
2
Order By: Relevance
“…In this study, fatty infiltration was determined based on the content FABP4 protein levels in the SS and DT muscles, which we found were comparable between the 2 muscles. This in contrast to a recent study by Lee et al, 25 which used a different and semiquantitative technique to assess FABP4 and demonstrated lower FABP4 levels, representative of the absence of fatty infiltration, in the DT muscle compared with the SS muscle. 25 These findings are in favor of the use of DT as a reference muscle.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, fatty infiltration was determined based on the content FABP4 protein levels in the SS and DT muscles, which we found were comparable between the 2 muscles. This in contrast to a recent study by Lee et al, 25 which used a different and semiquantitative technique to assess FABP4 and demonstrated lower FABP4 levels, representative of the absence of fatty infiltration, in the DT muscle compared with the SS muscle. 25 These findings are in favor of the use of DT as a reference muscle.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, fatty infiltration was determined based on the content FABP4 protein levels in the SS and DT muscles, which we found were comparable between the 2 muscles. This in contrast to a recent study by Lee et al, which used [50]. These findings are in favor of the use of DT as a reference muscle.…”
Section: Discussioncontrasting
confidence: 96%
“…However, given that the rapamycin derivates are clinically used as antitumor agents and exhibit various systemic side effects, the use of rapamycin to treat patients with RCT will not be clinically acceptable. Lee et al 11,12 showed that the expression of FABP4, a protein involved in fatty acid metabolism, is upregulated in patients with RCT and that targeting of FABP4 reduces fatty degeneration in a rat model. While this strategy may deserve further investigations, FABP4 inhibitors are not currently used clinically, and the potential adverse effects are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%